UGLEVОDORODLАR TEMАSÍN ОQÍTÍWDА KEYS STADI USÍLÍNAN PAYDALANÍW - Qutlimuratova, Shahnoza Aralbay qızı; Aytbaeva, Hurliman Berdax qızı; Aymurzaeva, Liza Gulmurzaevna (ILIM hám JÁMIYET, 2026)
The article examines the use of the case study method in teaching the topic of hydrocarbons, which is one of the important sections of chemistry in the system of general secondary education. The pedagogical potential of the case study method, its role in the educational process, and its significance in developing students’ analytical thinking are analyzed.